A non-damaging purification method: decoupling the toxicity of multi-walled carbon nanotubes and their associated metal impurities. Issue 6 (30th April 2019) - Darne, Christian; Desforges, Alexandre; Berrada, Nawal; Fontana, Caroline; Guichard, Yves; Gaté, Laurent; Bégin, Dominique; Le Normand, François; Valsaque, Fabrice; Ghanbaja, Jaafar; Gleize, Jérôme; Vigolo, Brigitte
Abstract : Toxicity induced by multi-walled carbon nanotubes and their metal impurities. Abstract : Multi walled carbon nanotubes (MWCNTs) are purified by a gas-phase method allowing selective removal of the metallic impurities (Fe and Al catalyst residues) while the MWCNTs remain untouched. Contrary to works using standard purification methods, our approach allows us to separately study toxicity due to metallic impurities and that of MWCNTs. Both raw and purified MWCNTs are thoroughly characterized by several techniques including transmission electron microscopy, Raman spectroscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy and adsorption volumetry. The results show that the purification method is efficient and the MWCNT characteristics are well controlled. We study the oxidative stress cell response induced by the MWCNT sample after purification. Cytotoxicity and genotoxicity are investigated using in vitro micronucleus and comet assays. Our results show that the metallic impurities of the used MWCNTs are not involved in the toxic potential of these CNTs. Consequently, these used CVD-produced MWCNTs alone are responsible for the observed toxic response. This presented approach, applied to other sources of CNTs, could be useful for determining the involvement of their metallic impurities in the observed toxic response.